Unbundled government : a critical analysis of the global trend to agencies, quangos and contractualisation - Pollitt, Christopher; Talbot, Colin (Routledge studies in public management, 2004)
This comprehensive study discusses the series of changes in governmental systems and structures. It considers the varying approaches of different countries and their governmental structures.